THU0532 Paediatric uveitis in french referral ophthalmologic centers: a descriptive analysis of 74 children. (15th June 2017) - Moal, L; Rousseau, A; Titah, C; Labetoulle, M; Bodaghi, B; Czitrom, S Guillaume
Abstract : Background: Uveitis in children is rare. Intensive interactions between ophthalmologists and paediatric rheumatologists are needed in order to choose the best therapeutic strategies for severe uveitis attacks. Objectives: Describe a cohort of 74 patients with paediatric uveitis. Methods: Retrospective analysis of children followed for uveitis before 18, by one paediatric rheumatologist (SGC) for systemic treatments' management and members of 3 ophthalmologic departments specialized in uveitis care in children (AR, CT, ML and BB) in Paris, during the 2006–16 period. Results: There were 74 paediatric uveitis, 42 anterior (57%, group1), 16 intermediate (21%, gr2), 7 posterior (9%, gr3) and 9 pan-uveitis (12%, gr4). Gender was equal in gr2–4, but there were more females in gr1. At presentation, mean ages were 8.6±4.1, 9.8±3.9, 9.1±3.6 and 10±4.2 years old. Mean follow-up was 3.7±3.7 years. JIA was the leading cause of gr1 uveitis (45%); gr2–3 uveitis were idiopathic in 81% and 86%, respectively. In gr4, etiologies were found in 7 out of 9 patients (Behçet-3, JIA-2, BBS-1, TINU-1). Conclusions: Paediatric uveitis induce a very high-level burden in children, even when anterior and sometimes despite optimal therapeutic management in tertiary care centers. Their early recognition and tight control in specialized units are absolutely required in order to decrease the level of definitive complications. Disclosure of Interest: None declared